PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN YAMAHA JUPITER MX DI KOTA DENPASAR - Bramantya, Yan Bayu; Jatra, I Made (E-Jurnal Manajemen, 2016)
Various motorcycle manufacturers competing to meet the needs of the market, carrying a variety of companies motorcycle trying to serve two-wheeler market by offering a wide range of product variants. Basic scientific work is to introduce the influence of Komenk as a celebrity endorser and brand image on purchasing decisions Yamaha Jupiter MX in Denpasar. The scientific work focuses on the study of Denpasar through data analysis technique multiple linear regression inclusion of samples obtained were 108 respondents using purposive sampling. Data to answer with the help of SPSS program proves celebrity endorser and the brand image simultaneously influence on purchasing decisions Yamaha Jupiter MX in Denpasar with a value of F (204.375) with sig (0,000). Celebrity endorser and the brand image of the partial significant positive effect on purchasing decisions Yamaha Jupiter MX in Denpasar.
Keywords: Celebrity Endorser, Brand Image, purchasing decisions